The population of W Ursae Majoris-type binaries in the solar neighborhood - Gazeas, K. (Contributions of the Astronomical Observatory Skalnate Pleso, 2020)
W Ursae Majoris-type binaries belong to the old population of our Galaxy, while their metallicity is close to solar. Their physical properties, kinematics and spatial distribution reflect the properties of their stellar progenitors. This study focuses on the spatial distribution of W UMa's in our solar neighborhood within a 500 pc radius, with a combined astrometric, photometric and spectroscopic determination of their stellar parameters. The sample is carefully selected, in order to fulfill certain criteria, and has well defined metallicity and distance parameters. H-R diagram, as well as similar correlation plots (mass-radius and mass-luminosity), show that the primary (more massive) components in such systems are located close or below the ZAMS region, while secondary components seem to be evolved, as a result of their common envelope geometry. Some prominent outliers are carefully examined in order to judge the environmental properties and evolution in certain locations of the Milky Way. It is found that metallicity is not correlated with distance, but there is a weak correlation between metallicity [M/H] and evolution state, as it is expressed by the location of the systems in the H-R diagram, the type of binary (A or W), and temperature.
Keywords: binaries: W UMa-type; stars: physical parameters; stellar evolution